Empoderamiento femenino y organización de las mujeres del Comité de Vaso de Leche del sector Nuevo Porvenir-2021 - Vega Varas, Laura Vanessa (2022)
The purpose of this research is to analyze the relationship between female empowerment and the organization of women members of the Comité de Vaso de Leche del Sector Nuevo Porvenir, in the district of El Porvenir, 2021 through the forms of promotion of the selfesteem and leadership (personal empowerment) and ways of promoting access to resources and exercise of rights (social empowerment). Ethnographic, inductive-deductive and statistical methods were applied, as well as observation, interview and survey techniques mainly. Among the main results, it was found that there are positive relationships between participation in the organization of the Comité de Vaso de Leche del Sector Nuevo Porvenir and the levels of empowerment through self-esteem, social contribution, entrepreneurship, leadership, search for means and resources subsistence as well as with regard to knowledge regarding their rights and active participation in enforcing them.